Identification and functional analysis of six DNAJ genes from Myzus persicae (Hemiptera: Aphididae) in response to UV-B stress - Long-Chun HE; Jian-Yu MENG; Guy SMAGGHE; Chang-Li YANG; Xue TANG; Chang-Yu ZHANG (European Journal of Entomology)
Ultraviolet B (UV-B) is a significant environmental factor affecting insect development, survival, and reproduction. DNAJ proteins are molecular chaperones found ubiquitously in insects that are crucial for their adaptation to environmental stresses. This study aimed to elucidate the roles of DNAJ genes in the response of Myzus persicae to UV-B stress. Herein, we identified six DNAJ genes in the aphid M. persicae, a devastating agricultural pest. We analyzed their expression profiles at different stages of development, in different tissues and for various durations of UV-B exposure. The expression levels of MpDNAJC30, MpDNAJC11, MpDNAJC2, and MpDNAJC3 were highest in wingless adults, while MpDNAJC9 and MpDNAJC17 were highest in second- and third-instar nymphs, respectively. Six MpDNAJs had higher expression levels in the epidermis and embryos, and lower levels in the head. Additionally, the expression levels of all genes increased significantly under different durations of UV-B exposure. Knockout of the DNAJ genes using RNA interference caused a significant decline in the survival rate, weight, body length, and body width of M. persicae exposed to UV-B radiation. Our research provides valuable insights into the stress response mechanisms of M. persicae, highlighting the importance of DNAJ genes in mediating their adaptation to UV-B stress.